2022
DOI: 10.1530/ec-22-0280
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender-affirming treatment on bone health in transgender and gender diverse youth

Abstract: Both in the US and Europe, the number of minors who present at transgender healthcare services before the onset of puberty is rapidly expanding. Many of those who will have persistent gender dysphoria at the onset of puberty will pursue long-term puberty suppression before reaching the appropriate age to start using gender affirming hormones. Exposure to pubertal sex steroids is thus significantly deferred in these individuals. Puberty is a critical period for bone development: increasing concentrations of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Puberty blockers have previously been considered a fully reversible treatment. Over the last decade, however, reports about adverse effects on bone density-leading in adult-hood to increased risk of fracture and kyphosis-have caused some practitioners to reconsider this view [18,19]. In the current study adverse effects on bone health (7/49; 14.3%) and on cardiovascular health (via weight gain, 5/49; 10.2%) have emerged as two key areas of concern.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Puberty blockers have previously been considered a fully reversible treatment. Over the last decade, however, reports about adverse effects on bone density-leading in adult-hood to increased risk of fracture and kyphosis-have caused some practitioners to reconsider this view [18,19]. In the current study adverse effects on bone health (7/49; 14.3%) and on cardiovascular health (via weight gain, 5/49; 10.2%) have emerged as two key areas of concern.…”
Section: Discussionmentioning
confidence: 85%
“…The physical effects of GnRH agonists have long been thought to be fully reversible: when ceased, puberty recommences. Recent data suggest a negative impact of long-term puberty suppression on bone mineral density (p. 1) [18,19]. Far less is known, however, about the effects of puberty suppression on cognitive, psychosocial and psychosexual development and mental health functioning [19][20][21].…”
mentioning
confidence: 99%
“…(10) Previous work showed that puberty suppression in transgender adolescents increased fat mass and decreased lean mass and that subsequent GAH shaped body composition toward the experienced gender. (11) With regard to bone, several studies recently reviewed in Ciancia and colleagues (12) reported a decrease in areal bone mineral density (aBMD) Z-scores after GnRHa administration, which was only partially restored after GAH administration. However, long-term outcome data in transgender individuals who started medical transition from the earliest stages of puberty onward are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a decrease in areal bone mineral density (aBMD) Z-scores were reported after GnRHa administration, which were partially restored after GAHT (13).…”
Section: Introductionmentioning
confidence: 99%
“…While much of what we know about GAHT in humans has focused on cardiovascular health and metabolic risk (13), the effect of delayed or prolonged pubertal suppression transitioned into GAHT on bone health is underappreciated. Previously, a decrease in areal bone mineral density (aBMD) Z-scores were reported after GnRHa administration, which were partially restored after GAHT (14).…”
Section: Introductionmentioning
confidence: 99%